Modification in structure of La and Nd co‐doped epitaxial BiFeO3 thin films probed by micro Raman spectroscopy. (28th April 2015) - Ahlawat, Anju; Satapathy, S.; Sathe, V. G.; Choudhary, R. J.; Singh, M. K.; Kumar, Ravi; Sharma, T. K.; Gupta, P. K.
<x xml:space="preserve">Abstract</x> The influence of La and Nd co‐substitution on structure, electric and magnetic properties of epitaxial thin films of BiFeO3 (BFO) was examined. We demonstrate structural phase transition in co‐doped La and Nd BFO thin films using Raman spectroscopy. Based on group theoretical analysis of the number and symmetry of Raman lines, we provide strong experimental evidence that the structure has been changed from rhombohedral to monoclinic due to co‐doping in BFO. The change in structure was also reflected in morphology of these films. Room temperature magnetic hysteresis curves showed that doped films exhibit enhanced ferromagnetic properties with remnant magnetization of 10 emu/cm3 and coercive field of 1.2 kOe. The enhanced magnetic properties highlight the potential applications of doped BLNFO thin film for smart devices. Copyright © 2015 John Wiley & Sons, Ltd.